IMPROVEMENT OF STAPLE LINE REINFORCEMENT METHODS AND EVALUATION OF THEIR EFFECTIVENESS - Prof., D.M.S. Teshaev O.R; PhD Ruziyev U.S; Niyazova N.R (Scholar Express Journals, 2025)
The aim is to improve the results of using staple sutures (SS)
Keywords: improve; staple; sutures